Idiopathic chilblain: a case series from Injibara General Hospital, Ethiopia - Tegegnie, Alemu Bezabih; Alene, Tamiru; Sineshaw, Meaza Molla (Frontiers in Medicine, 2025)
BackgroundIdiopathic chilblains are inflammatory lesions on the skin that typically appear after being in a cold, wet environment. The condition manifests itself as burning, soreness, and pruritis in the extremities (fingers and toes), usually occurring 12 to 24 h following a triggering event. Conservative measures are the mainstay of treatment for idiopathic chilblain; however pharmaceutical therapy may be necessary in cases that are severe or persistent. This is the only case series in Ethiopia concerning idiopathic chilblain.Case presentationFrom June to August of 2024, 12 individuals in the dermatology department of Injibara General Hospital in Ethiopia were diagnosed with idiopathic chilblain. Nine (or 75%) of these patients were women. This study’s mean age at diagnosis was 23.2 years (range: 3–55 years). All cases presented with itching sensations and/or pain. Only a few patients presented with swelling and color change during cold exposure. One patient presented with ulceration involving the tip of the digits. Most patients were prescribed clobetasol propionat and oral nifedipine. Others were treated with only topical corticosteroids, and few refused any medical treatment. All patients were counseled to avoid cold and keep extremities warm. Only one patient has persistent disease and the rest have completely improved.ConclusionAccording to the current study, young women were the group most frequently impacted by idiopathic chilblain. Idiopathic chilblain in Ethiopia is underreported, necessitating comprehensive studies involving larger patient numbers and a focus on prevalence, diagnosis, treatment, and psychosocial impact.